Measurement of inclusive rho(0), f(0)(980), f(2)(1270), K-2(*0)(1430) and f '(2)(1525) production in Z(0) decays - Abreu, P; Adam, W; Adye, T; Adzic, P; Ajinenko, I; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; et al. (1999)
DELPHI results are presented on the inclusive production of the neutral mesons ρ0, f0(980), f2(1270), K2*0(1430) and f2′(1525) in hadronic Z0 decays. They are based on about 2 million multihadronic events collected in 1994 and 1995, using the particle identification capabilities of the DELPHI Ring Imaging Cherenkov detectors and measured ionization losses in the Time Projection Chamber. The total production rates per hadronic Z0 decay have been determined to be: 1.19 ± 0.10 for ρ0; 0.164 ± 0.021 for f0(980); 0.214 ± 0.038 for f2(1270); 0.073 ± 0.023 for K2*0(1430); and 0.012 ± 0.006 for f2′(1525). The total production rates for all mesons and differential cross-sections for the ρ0, f0(980) and f2(1270) are compared with the results of other LEP experiments and with models. © 1999 Elsevier Science B.V. All rights reserved.